EVIDENCE FOR AN ACIDIC OCEAN ON MARS FROM PHOSPHORUS GEOCHEMISTRY OF MARTIAN SOILS AND ROCKS - Greenwood J.P.; Blake R.E. (My University, 2006)
Recent analyses of elemental concentrations and mineralogy of iron-bearing compounds of Martian soils and rocks by the Mars Exploration Rovers at Meridiani Planum and Gusev Crater demonstrate that phosphorus concentration is correlated with sulfur and chlorine. The positive correlation of these three elements with each other in soils at both sites argues for a globally homogeneous soil component. Sulfur, and possibly chlorine, in Martian soils and Meridiani Planum outcrop rocks is likely derived from volcanic exhalations, but phosphorus must be derived from the weathering of igneous rocks. Here we show that the similar concentration of phosphorus in soils at the two Mars Exploration Rover sites, coupled with positive correlations to chlorine and sulfur, is best explained as resulting from mixing and homogenization of phosphate, sulfate, and chloride in a large acidic aqueous reservoir, such as an acidic ocean. Acidic thin-film or acid-fog weathering cannot readily produce the similar P/S and P/Cl ratios of soils measured on Mars, and more important, cannot explain the high phosphorus content of ancient (ca. 3-4 Ga) sulfate-rich rocks in outcrop at Meridiani. The existence of a global acidic hydrosphere or ocean at some time in early Martian story can also explain the lack of extensive carbonate deposits on the Martian surface. © 2006 Geological Society of America.
Keywords: ACID WEATHERING; MARS; MARTIAN SOIL